Design of an inventory management system in an agricultural supply chain considering the deterioration of the product: The case of small citrus producers in a developing country - Acosta, Cristhian Guillermo; Cano, Andrés Felipe; Peña, Diego Leon; Rivera, Leonardo; Bravo, Juan José (Journal of Applied Engineering Science, 2018)
Inventory management along the agrifood supply chain is a subject of great interest due to the constraints related with the perishable condition of product. Significant problems like demand forecasting, inventory management and transportation was evidenced within the supply chain studied. Additionally, the management of perishables and their lifecycle are the most frequently issue in this kind of supply chain. An inventory management policy is defined taking in consideration the optimal quantity for an order and the time for ordering so as to ward off costs related with understock or overstock. This paper presents a mathematical model for inventory management in agricultural supply chains considering perishability. The supply chain studied involves a retailer, a producer and a supplier. The advantages of integrating inventory management along the supply chain are discussed and finally some recommendations and research opportunities set forth.